Design and Development of a Web-based Temple Appointment System - Chai Zhi Qing,; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2023)
Temple Appointment System is a web-based system for visitors to make an appointment for prayer. Currently, visitors contact the temple by phone to make an appointment but it is not very effective as sometimes the staff missed the call due to insufficient of staff. The aim of this project is to ease all the Buddhists in making a new booking to the temple and also enable the staff of Tham Sen Temple to create a new event on a certain day for visitors to make prayer appointments. The project is implemented using Prototype model. The system is developed using Visual Studio Code and XAMPP, which used PHP language as the back-end. After the implementation phase, functional testing and user acceptance testing are performed. System testing showed that the actual results of the test plan for each module were successful. All respondents are satisfied with the user interface and system functionalities.